The role of the classroom's images. Study of visual culture at three schools. Issue 2 (3rd April 2019) - Alonso Sanz, Amparo; Jardón, Paula; Lifante Gil, Yolanda
Abstract : This research forms part of the project titled: 'Aesthetic quality research of three Valencian schools', that analyses the effects in detail that images displayed in schools have, as a variable in evaluating educational quality. Through applying Arts Based Educational Research, images displayed on 29 classroom walls in three schools were photographed and analysed based upon their function; they were subsequently classified as educational images, academic images, and comfort-generating images. The results of this research show quantitative, qualitative, and aesthetic values of this visual heritage by using photographic series that are laid out in a chart-like manner, creating a visual message for each classroom. Upon observing these typologies, one perceives: the predominate utilisation of the image and its aesthetics; the differences in visible occurrences between subject matters displayed on the walls; the teacher's intentions when displaying the images. In the conclusions, alternatives are proposed for improving the schools' aesthetical qualities.